Evaluating efficacy and outcomes: comparison of laser treatment and crystallized phenol in pilonidal sinus disease - Emral, Ahmet Cihangir; Gülen, Merter; Ege, Bahadır (Frontiers in Surgery, 2025)
ObjectiveThe aim of this study is to comprehensively evaluate the efficacy of laser ablation and crystallized phenol application in the treatment of pilonidal sinus disease, focusing on treatment success, recurrence rates, complications, and the patients' return to normal life.Material and methodData from patients treated for pilonidal sinus disease with laser ablation and crystallized phenol application at our clinic between January 2020 and September 2023 were retrospectively reviewed. Preoperative data including pit counts, disease stage, preoperative pilonidal abscess history, disease duration (week), treatment success, recurrence/persistent disease, postoperative complications, healing time (days), and visual analogue scale (VAS) scores on postoperative days 1 and 7, as well as return to normal life (days), were analyzed.ResultsA total of 121 patients were included in the study, with 51 receiving laser ablation and 70 receiving crystallized phenol application. The postoperative outcomes revealed that the wound healing period and postoperative VAS values were statistically significantly better in the laser ablation group.ConclusionWound healing was faster and postoperative pain was less in the laser group compared to the phenol group. According to this study, both methods can successfully treat the disease in selected cases.